PP047 Intravenous Iron Sucrose Therapy In Real-World Anemic Patients. (12th January 2018) - Alcobia, Armando; Soares, Ana; Delerue, Maria Francisca; Mansinho, Hélder; Pereira, Hélder; Ferreira, Diana; Plácido, Madalena; Afonso-Silva, Marta; Gomes, Marta Vargas; Amorim, Miguel; Pinto, Beatriz; Moura, Carlota; et al.
Abstract : INTRODUCTION: Anemia is a major problem, frequently resulting from iron deficiency (1). Guidelines recommend the administration of intravenous (IV) iron, leaving blood transfusions for critical patients due to the potential impact in length of stay (LOS) and mortality (2, 3). We aimed to characterize IV iron sucrose utilization and health resource utilization in anemic patients. METHODS: This is a retrospective ongoing cohort study. Patient records from a general Portuguese Hospital with an administration of iron sucrose in 2014–2015 were reviewed. Adult anemic patients with at least one hemoglobin (Hb) evaluation before and after the administration of IV iron were included. Endpoints assessed were: Hb level (baseline, 4 and 8 weeks after), anemia correction rate at weeks 4 and 8, blood transfusions, length of stay (LOS), rate of readmissions (<30 days) and inpatient mortality. Statistical analysis included non-parametric and chi-square tests to assess differences between groups and a logistic regression model, using a 5 percent significance level. RESULTS: Data was collected for 401 patients (63.1 percent female; mean age Standard Deviation, SD: 62.6 (21.7) years) and 431 IV iron sucrose administration episodes. Mean cumulative iron dose was 679.5 mg. Baseline Hb level was 84.5 g/l and increased to 94.3 g/l (week 4) and to 103.0 g/l (week 8). Blood transfusions were performed in 53.8 percent of the episodes. Overall 157 (36.4 percent) episodes had a >20 g/l increase in Hb level. Blood transfusions were associated with a higher proportion of Hb level increase >20 g/l (44.0 percent versus 27.9 percent, p<.001). The overall mean LOS was 15.3 days, although episodes with transfusions had a significantly longer duration (17.5 days versus 12.7 days; p<.001). Overall readmission rate was 25.8 percent, with a higher proportion in episodes with blood transfusions (29.3 percent versus 21.6 percent). A total of 36 patients (9.0 percent) died at the hospital before discharge. Transfusions performed during or after IV iron administration increased 3.1 times the risk of in-hospital death (95 percent Confidence Interval, CI: 1.3-7.0; p = .008), after adjusting for age and sex. CONCLUSIONS: We observed a high rate of blood transfusions in this cohort treated with intravenous iron sucrose for anemia. Transfusions were associated with substantial burden of resource consumption and in-hospital mortality.